The Greater Roman Historians - Laistner, M. L. W. (Berkeley, CA : University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1947. This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived.
Frontmatter -- PREFACE -- CONTENTS -- CHAPTER I. THE HELLENISTIC BACKGROUND -- CHAPTER II. ROMAN HISTORIANS TO THE DEATH OF CAESAR -- CHAPTER III. SALLUST -- CHAPTER IV. LIVY, THE MAN AND THE WRITER -- CHAPTER V. LIVY, THE HISTORIAN -- CHAPTER VI. TACITUS AND HIS FORERUNNERS -- CHAPTER VII. TACITUS, THE HISTORIAN -- CHAPTER VIII. AMMIANUS MARCELLINUS -- NOTES -- INDEX OF QUOTED ANCIENT AUTHORS -- GENERAL INDEX
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Okt 2020).
JSTOR
Keywords: Historians -- Rome; Rome -- Historiography; Historiens -- Rome; NON-CLASSIFIABLE.; HISTORY / Ancient / Rome; Historians; Historiography; Rome (Empire)